Omadacycline Is Highly Active In Vitro against Mycoplasma genitalium - Ken B. Waites; Donna M. Crabb; T. Prescott Atkinson; William M. Geisler; Li Xiao (Microbiology Spectrum, 2022)
ABSTRACT Here, we performed in vitro susceptibility testing on 10 Mycoplasma genitalium isolates against omadacycline, minocycline, tetracycline, doxycycline, moxifloxacin, levofloxacin, and azithromycin. Omadacycline was the most potent agent, with all MICs of ≤0.5 μg/mL. MICs were not affected by resistance to other agents, including resistance to other tetracycline class drugs. Omadacycline may be a potential treatment option for M. genitalium infection. IMPORTANCE There are very few clinical isolates of Mycoplasma genitalium available for in vitro susceptibility testing. We studied 10 isolates and determined that the new semisynthetic aminomethylcycline omadacycline is active against isolates that are resistant to tetracyclines, macrolides, and quinolones. These data suggest that clinical studies should be performed in order to see if omadacycline may be useful to treat urogenital infections caused by M. genitalium.